ANALISIS KRITIKAN PENGGUNA MEDIA SOSIAL TERHADAP KINERJA PEMERINTAH KOTA SAMARINDA [Analysis of Criticism the Use of Social Media Toward Performance of Goverment in Samarinda City] - Ali Kusno (TOTOBUANG, 2016)
Samarinda citizens were critical toward the performance of government. Citizens critical were seen through  the language that they used in social media, one of facebook’s group Samarinda Community (Facebook Bubuhan Samarinda). The use of language as criticism was important to be examined. The purpose of this research revealed textual analysis (micro), the dimensions of discourse practice, and the dimensions of discourse practice (macro). The approach of this research was critical discourse analysis. The research data in the form of copy of the group’s members uploaded at Facebook’s group Samarinda Community. The result showed: First, textual analysis (Micro Analysis). Generally, the text structure was divided into three parts, the opening, the content, and the closing. The opening related to the target critical and the meaning of critical regarding. The rest, the critics expressed their criticism directly on the substance. In the closing, the criticism was using argumentative with a variety expression, such as hopelessness, irritability, and anger. Generally, they use of transitive grammar. The critical was containing negative things of Mayor and staffs. The use of criticism vocabularies had characteristics that were criticizing directly, advising, using abusive language, teasing allusion, and accusing. Second, discourse practice dimension. Various complaints had been an accumulation over various issues. The criticism had positive impact on the improvement of Samarinda. Third, social and cultural practice dimension (macro).  Overall identifiable ideologies were built, such as the Mayor of Samarinda was not able to manage the government. The government was anti critical, not an independent, didn’t has the concept to build Samarinda.       Warga Samarinda kritis terhadap kinerja Pemerintah Kota. Kekritisan warga tampak dalam penggunaan bahasa di media sosial, salah satunya grup facebook Bubuhan Samarinda (FBM). Penggunaan bahasa kritikan tersebut penting untuk dikaji. Tujuan penelitian ini mengungkapkan analisis tekstual (mikro), dimensi praktik wacana, dan dimensi praktik wacana (makro). Pendekatan penelitian ini berupa analisis wacana kritis. Data penelitian berupa salinan unggahan anggota grup FBM. Hasil penelitian menunjukkan bahwa: pertama, Analisis Tekstual (Analisis Mikro). Struktur teks secara umum dibagi menjadi tiga bagian, yaitu bagian pembuka, bagian isi, dan bagian penutup. Pembuka teks terkait dengan target kritikan dan perihal kritikan yang dimaksud. Selebihnya pengkritik menyampaikan kritikan langsung pada substansi. Penutup kritikan menggunakan argumentatif dengan beragam ekspresi, seperti keputusasaan, kejengkelan, dan kemarahan. Penggunan gramatika transitif secara umum kritikan yang dilontarkan berisi hal-hal negatif  Walikota Samarinda beserta jajaran. Penggunaan kosakata kritikan, memiliki kekhasan, yakni mengkritik secara langsung, dengan menasihati, bahasa kasar, sindiran, dan juga menyerang/menuduh; Kedua, Dimensi Praktik Wacana. Berbagai kritikan yang dilontarkan merupakan akumulasi atas berbagai persoalan.  Kritikan memberikan dampak positif untuk pembenahan Kota Samarinda; Ketiga, Dimensi Praktik Sosial Budaya (Makro). Secara keseluruhan dapat diidentifikasi ideologi yang dibangun, seperti Walikota Samarinda tidak mampu mengelola pemerintahan; Pemerintah Kota Samarinda antikritik, tidak independen, tidak memiliki konsep membangun Kota Samarinda.